2016
DOI: 10.1080/14767058.2016.1182980
|View full text |Cite
|
Sign up to set email alerts
|

Maternal social support, quality of birth experience, and post-partum depression in primiparous women

Abstract: Social support perceived by mothers during pregnancy plays a significant role as a protection factor against post-partum depression, both directly and indirectly, reducing the negative clinical aspects of the birth experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 13 publications
(14 reference statements)
11
82
0
1
Order By: Relevance
“…Numerous clinical aspects related to the occurrence of PPD in women have been found in the scientific literature (complicated and prolonged labour, obstetric interventions during labour, pain, postpartum complications) [23]. This study confirmed the relationship between women's multiparity and the severity of depressive symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…Numerous clinical aspects related to the occurrence of PPD in women have been found in the scientific literature (complicated and prolonged labour, obstetric interventions during labour, pain, postpartum complications) [23]. This study confirmed the relationship between women's multiparity and the severity of depressive symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, partner's support resulted to mediate the relation between pregnant women's concerns and their psychological well-being (Ilska and Przybyła-Basista, 2017). Moreover, the social support perceived by mothers during pregnancy represented a protective factor against postpartum depression while also reducing the negative aspects of the experience of childbirth (Tani and Castagna, 2017).…”
Section: Psychological Well-being Of Expectant Mothersmentioning
confidence: 97%
“…Different intrapartum factors can affect the experience of traumatic childbirth. For example, fear of childbirth, failure to take analgesics [9], lack of support [10], and transferring the newborn to the Neonatal Intensive Care Unit (NICU) [11] can be among risk factors for traumatic childbirth. In a cross sectional study among 800 Iranian women, absence of pain relief during labour and the fear of childbirth were the main intrapartum predicting factors for a traumatic birth experience [9].…”
Section: Introductionmentioning
confidence: 99%